Polyphenolic Composition of Lentil Roots in Response to Infection by Aphanomyces euteiches - Bazghaleh, Navid; Prashar, Pratibha; Purves, Randy W.; Vandenberg, Albert (Frontiers in Plant Science, 2018)
Polyphenols comprise the largest group of plant secondary metabolites and have critical roles in plant physiology and response to the biotic and abiotic environment. Changes in the content of polyphenols in the root extracts and root tissues of wild (Lens ervoides) and cultivated (Lens culinaris) lentil genotypes were examined in response to infection by Aphanomyces euteiches using liquid chromatography mass spectrometry (LC-MS). Genotype, infection and their interaction determined the composition of polyphenols in lentil roots. The levels of several polyphenols were lower in the root extract of the low-tannin genotype Lens culinaris ZT-4 compared to Lens ervoides L01-827A. Kaempferol derivatives including kaempferol dirutinoside and kaempferol 3-robinoside 7-rhamnoside were more concentrated in the healthy root tissues of Lens ervoides L01-827A than in Lens culinaris genotypes. Infection increased the concentration of kaempferol, apigenin, and naringenin in the root tissues of all genotypes, but had no effect on some polyphenols in the low-tannin genotype Lens culinaris ZT-4. The concentrations of apigenin, naringenin, apigenin 4-glucoside, naringenin7-rutinoside, diosmetin, and hesperetin 7-rutinoside were higher in the infected root tissues of Lens ervoides L01-827A compared with the Lens culinaris genotypes. Organic acids including coumaric acid, vanillic acid, 4-amino salicylic acid, 4-hydroxy benzoic acid, and 3,4-dihydroxy benzoic acid effectively suppressed the in-vitro hyphal growth of A. euteiches. Some of these bioactive polyphenols were more concentrated in roots of Lens ervoides L01-827A but were low to undetectable in ZT-4. This study shows that genotypic differences exist in the composition of root polyphenols in lentil, and is related to the response to infection caused by A. euteiches. Polyphenols, particularly the organic acid content could be useful for selection and breeding of lentil genotypes that are resistant to Aphanomyces root rot disease.